2021
DOI: 10.15421/022150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on sporulation of Eimeria arloingi and Eimeria perforans oocysts

Abstract: Eimeriosis of farm animals is one of the most widespread parasitic diseases in the world. In the conditions of the steppe zone of Ukraine Eimeria perforans is more common in rabbits and E. arloingi in sheep and goats. Study of factors which influence the development of these protists on the soil surface is one of the major challenges for veterinarians working for large livestock companies and fighting against eimeriosis. Environmental temperature is able to change the speed of sporulation of oocysts Eimeria. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…During the migration through food chains, those sub-stances end up in the organisms of animals and contaminate agricultural products [29,30]. Over recent years, alternative substances to combat pests have become broadly distributed: there are compounds that already exist in nature, such as medicinal plants [45][46][47], their essential oils [48,49], and also substances used in the food industry [50,51]. Some inorganic food additives, including alkalis, acids and salts may have negative effects on nematode larvae-parasites of agricultural animals.…”
Section: Discussionmentioning
confidence: 99%
“…During the migration through food chains, those sub-stances end up in the organisms of animals and contaminate agricultural products [29,30]. Over recent years, alternative substances to combat pests have become broadly distributed: there are compounds that already exist in nature, such as medicinal plants [45][46][47], their essential oils [48,49], and also substances used in the food industry [50,51]. Some inorganic food additives, including alkalis, acids and salts may have negative effects on nematode larvae-parasites of agricultural animals.…”
Section: Discussionmentioning
confidence: 99%
“…Boyko et al, reported the activity of various plant species having essential oils toward sporulation inhibition of Eimeria [33]. The results were essential oil from Syzygium aromaticum exerted a 54% killing effect on the sporulated oocysts and the sporulated oocysts presence was found be zero [33]. These findings suggest that the essential oil exerted its action through the alteration of the cell wall and sporulation process.…”
Section: Effect On Sporulation and Iamentioning
confidence: 99%
“…In this study, the oocysts were treated with various concentrations of P. emblica, and an almost 35% reduction of sporulated oocysts was observed. Boyko et al, reported the activity of various plant species having essential oils toward sporulation inhibition of Eimeria [33]. The results were essential oil from Syzygium aromaticum exerted a 54% killing effect on the sporulated oocysts and the sporulated oocysts presence was found be zero [33].…”
Section: Effect On Sporulation and Iamentioning
confidence: 99%
“…Cho et al (2006) reported that yeast extracts rich in nucleotides had a positive impact on the intestinal mucosa and its lymphoid formations, contributing to the development of local immunity. In recent years, the use of phytogenic feed additives, which contain a wide range of herbs, spices, and essential oils, has become relevant (Zazharskyi et al, 2019;Boyko et al, 2021;Lieshchova & Brygadyrenko, 2022Bilan et al, 2023). Scientists believe the possible mechanisms of action of plant extracts on animals are related to the intestinal microflora correction, increased absorption and nutrient assimilation, as well as pronounced antioxidant and immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%